Golgi phosphoprotein 3 (GOLPH3) promotes hepatocellular carcinoma cell aggressiveness by activating the NF‐κB pathway. Issue 3 (February 2015) - Dai, Ting; Zhang, Dongsheng; Cai, Muyan; Wang, Chanjuan; Wu, Zhiqiang; Ying, Zhe; Wu, Jueheng; Li, Mengfeng; Xie, Dan; Li , Jun; Song, Libing
Abstract Hepatocellular carcinoma (HCC) is one of the most lethal malignancies, in which the NF‐κB pathway plays an important role and is constitutively activated. Better understanding of the molecular pathogenesis of HCC and the NF‐κB pathway are needed to improve patient outcomes. Herein, we identified an unappreciated protein involved in NF‐κB‐induced activation, Golgi phosphoprotein 3 (GOLPH3). The mRNA and protein expression levels of GOLPH3 were frequently up‐regulated in HCC and GOLPH3 expression correlated closely with clinical stage and survival in both the testing and validation cohorts. Ectopic over‐expression of GOLPH3 in PLC/PRF/5 (PLC) and Huh7 HCC cells protected against cisplatin‐induced apoptosis, promoted angiogenesis and proliferation and increased the aggressiveness of HCC cells in vitro and in vivo, whereas inhibition of GOLPH3 led to decreased aggressiveness. Through analysis of two published HCC patient profiles, GOLPH3 expression significantly correlated with NF‐κB signalling. Furthermore, we demonstrated that GOLPH3 promoted K63‐linked polyubiquitination of tumour necrosis factor receptor‐associated factor 2 (TRAF2), receptor interacting protein (RIP) and NF‐κB essential modulator (NEMO) and substantially sustained the activation of NF‐κB in HCC cells. Taken together, our findings provided evidence that GOLPH3 is a prognostic and/or potential therapeutic biomarker for HCC patients and plays an important role in activation of the NF‐κB pathway during HCC progression. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.